Neoplasm Risk in Rheumatic Diseases Has No Correlation With Conventional Synthetic Disease-Modifying Anti-rheumatic Drugs Usage—A Population-Based Nested Case–Control Study - Cai, Shaozhe; Perng, Wuu-Tsun; Huang, Jing Y.; Chiou, Jeng-Yuan; Dong, Lingli; Wei, James C. (Frontiers in Medicine, 2020)
Abstract Objectives: To investigate whether there is an elevated neoplasm risk in patients with rheumatic diseases treated with conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs). Methods: A population based nested case-control study was performed by retrieving all patients newly diagnosed as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and psoriatic arthritis (PsA) or psoriasis vulgaris (PsO) from the 2000 Longitudinal Health Insurance Database (LHID 2000) in Taiwan. 261 patients with neoplasm from 1997 to 2013 were enrolled in this study, and controls were matched in a 1:1 ratio with age, sex and year of enrollment. Composition of demographic indices, comorbidities, medication usage and differences in days of prescription of different medications between neoplasm and neoplasm-free (control) groups were compared. Results: Between control and neoplasm group, no differences in ratio were observed in the usage of hydroxychloroquine (50.96% vs. 49.04%, p=0.6616), methotrexate (26.82% vs. 27.59%, p=0.8441), azathioprine (3.45% vs. 3.07%, p=0.8052) and cyclophosphamide (1.15% vs. 2.30%, p=0.3131) from enrollment to index date. Medications within 3 years before index date in patients had >=3 months of comparable duration also showed no difference.(Hydroxychloroquine: 33.06% vs 30.25%, p=0.6404; Methotrexate: 20.66% vs 25.21%, p=0.4018; Azathioprine: 2.48% vs 2.52%, p=0.9835; Cyclophosphamide: 0.83% vs 0.84%, p=0.9906). We also made a subgroup analysis focusing on RA and SLE patients, and no difference between control and neoplasm group, in both the ratio of usage and days of prescription of hydroxychloroquine, methotrexate, azathioprine, and cyclophosphamide was observed. Conclusion: Neoplasm risk in patients with rheumatic diseases has no correlation with csDMARDs usage.